Pathological Manifestations And Damage Map: Case Study Of The Duarte Coelho Bridge Located In The City Of Recife/PE - Teixeira, Igor Albuquerque da Rosa; Nascimento , Carlos Fernando Gomes do; Gonzaga, Camila Marques do Régo; Albuquerque , Everson Silva de; Monteiro , Eliana Cristina Barreto (Technical and Scientific Journal Green Cities, 2024)
Bridges play a crucial role in the logistics of the Recife Metropolitan Region – (RMR), which influences the modernity of the city’s architecture and landscaping. Due to the importance of these structures for the city’s growth, it is essential to carry out studies that make it possible to better understand the current state of conservation of the bridge. The present study sought to investigate the recurrent pathological manifestations in the structure of the Duarte Coelho Bridge located in Recife/PE, which helped in the development of the damage map. To carry out this survey, visual inspections were carried out using identification sheets of all damages that describe the current situation and recorded through photographs and images obtained by the Unmanned Aerial Vehicle (UAV) camera. The damage map was created with the help of AutoCAD software from the registered data specifying the specific damages. Through on-site analyses, it was observed that the majority of pathological manifestations could be mitigated through prevention and management measures for periodic maintenance. The bridge is in a moderate state of conservation and, based on the damage map prepared, it was observed that the most recurrent pathological manifestations were: mold and mildew, damp spots, efflorescence, fissures, concrete spalling and reinforcement corrosion. The analysis carried out allowed us to visualize the precariousness, highlighting the need for repairs and the creation of a preventive maintenance plan. Prevention prevents the recurrence of these anomalies, ensuring the safety and durability of structures, in addition to preserving the logistical and functional importance of bridges for society.